Experimental Research on the Co-deflagration Characteristics of a Mixture of Coal Powder and Corn Starch in an Air/methane Atmosphere. Issue 5 (4th April 2023) - Lin, Song; Liu, Zhentang; Qian, Jifa; Chu, Xiaomeng; Gu, Zhoujie
ABSTRACT: To investigate co-deflagration effect of a mixture of coal powder and corn starch, an air/methane atmosphere test was performed in a vertical explosion tube device and a 20-L spherical explosion device. Compared with pure coal powder and corn starch, the powder mixture undergoing deflagration in air was characterized by more uniform-distributed flame brightness, a more continuous flame structure, and less fluctuating flame propagation, approaching the fastest propagation velocity before mixing. Under the same mass concentration, the deflagration pressure of the powder mixture in methane atmosphere is related to the mixing proportion and is between the respective pressures of the two kinds of powder. P m and (d P /d t )m of the mixtures of methane and different powders show overall consistency with increasing equivalence ratios, however, different powders with the same equivalence ratio still differ in their characteristic deflagration parameters.